Bukan Sekadar Boneka: Pemaknaan Fans Stray Kids pada Tren Mengoleksi SKZOO Ditinjau dari Budaya dan Ekonomi Penggemar - Cinti, Putu Intan Raka (Universitas Gadjah Mada, 2025)
This study aims to understand how Stray Kids fans interpret the activity of collecting SKZOO dolls through the lens of fan culture and fan economy. Using a phenomenological approach, this research explores fans subjective experiences in perceiving SKZOO dolls not merely as consumer goods, but as a medium for gaining emotional needs, a symbols of identity, and a form of participation in fandom culture. The findings reveal that fans love to collect SKZOO dolls because of the cuteness as a representation of kawaii culture, strenghthening the emotional bonds both among fans and with Stray Kids,, while simultaneously becoming part of participatory culture through content creation and distribution. On the other hand, SKZOO dolls also embodies the dynamics of fans economy through hypercommercialization, where entertainment companies capitalize on fans’ emotional attachment to encourage repetitive consumption. Thus, these SKZOO dolls emerge as a dual phenomenon: a medium of fan cultural expression and an instrument of the entertainment industry for gaining finansial profit.